Sistem Keamanan Helm Berbasis Internet of Things dengan Fitur Pelacakan Menggunakan Android - Panji Wiratama Santoso; I Nyoman Piarsa; Ni Made Ika Marini Mandenni (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2021)
Helmet theft is a problem that is of concern to the public. Information Technology provides may resolve any problems, like Internet of Things-based system that can detect helmet theft and track the location of the helmet if it's stolen. This system is designed using a microcontroller device, namely Arduino which is attached to the helmet and motorbike with the help of the SIM800L v2, GPS Neo-6m, buzzer, and Bluetooth HC-05 which is connected to the master slave as an indicator of the safety of the helmet. The hardware on the helmet is connected to Firebase Realtime Database server so it can be connected with the user's Android application to monitor the state and location of the helmet. Android application displays maps to determine the position of the helmet, and can display notifications when the helmet is being stolen. The conclusion is this system can detect helmet theft with a maximum distance from the master and slave bluetooth connections of 10 meters, and the average data transmission from hardware to Firebase is 1,1 seconds, and can monitor status of the helmet and track the position of the helmet through the Android application with Android Jelly Bean (v4.3) operating system.